Հայկ Խաչատրյանի «Գրիգոր Մագիստրոսի վերջին թուղթը» պատմավեպը - Ժաննա Բեգլարյան (ՀՀ ԳԱԱ հրատ.)
В статье рассматривается роман А. Хачатряна «Последнее письмо Григора Магистроса», историческая эпоха, идея и образ героя одноименного романа. Выявляется научный материал, служащий основой исторического романа. Zhanna Beglaryan, in this article considers Hayk Khachatryan’s historical novel “The Last Paper of Grigor Magistros ” and imparts the scientific material constituting the basis for the novel.
Keywords: Language and Literature